Analysis of Road Damage Levels Using the SDI (Surface Distress Index) Method for Evaluation and Handling of Potholes - Prayudyanto, Muhammad Nanang; Rulhendri, Rulhendri; Syaiful, Syaiful; Ramadan, Riki Natanael (ASTONJADRO, 2024)
Highways are land transportation infrastructure that is very important in facilitating economic relations activities. The method used is the SDI (Surface Distress Index) method. The purpose of this study is to identify the types of road damage, analyze the level of road damage using the SDI method and evaluate the SDI value and handling potholes. The length of the road studied in this research is 1000 ± m which is divided into 10 segments with a segment length of 100 m each. The data required for this research is secondary data and primary data. Based on the results of processed field data, 6 types of road damage were obtained. The percentage results on Jalan Ciremai Ujung with an average SDI value of 34 and categorized as having a value in good and moderate conditions so that the percent value (%) in damaged conditions is 90%, moderate 10%, slightly damaged 0% and seriously damaged 0%. And carry out handling by means of routine maintenance on segments 1,2,3,5,6,7,8,9,10 and periodic maintenance on segment 10.